2013
DOI: 10.1080/19768354.2013.865675
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational effects of paternal alcohol exposure in mouse offspring

Abstract: Experimental animal studies and epidemiologic investigations report the developmental toxicity associated with alcohol that paternal alcohol consumption caused retardation of growth, malformations, reduction of body weight, and mortality in offspring. Although numerous studies on paternal alcohol exposure showed transgenerational effects, the toxic effects varied widely due to differences in the way of exposure to alcohol, and in the endpoints assessed in each study. In the current study, we investigated trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…Independent of whether both WT parental sexes or only one parental sex were exposed to MPH, the untreated WT F1 offspring showed increased activity compared to offspring from a cross between WT parents from the control treatment ( Figure 3A). This is consistent with findings from other studies using animal models to investigate cross-generational effects of psychoactive drugs (Bingsohn et al 2016), alcohol (Lee et al 2013;Yohn et al 2015), environmental toxins (Carvan et al 2017;Knecht et al 2017), and drug stimulants (Yohn et al 2015).…”
Section: Mph Has Cross-generational Behavioral Effectssupporting
confidence: 91%
“…Independent of whether both WT parental sexes or only one parental sex were exposed to MPH, the untreated WT F1 offspring showed increased activity compared to offspring from a cross between WT parents from the control treatment ( Figure 3A). This is consistent with findings from other studies using animal models to investigate cross-generational effects of psychoactive drugs (Bingsohn et al 2016), alcohol (Lee et al 2013;Yohn et al 2015), environmental toxins (Carvan et al 2017;Knecht et al 2017), and drug stimulants (Yohn et al 2015).…”
Section: Mph Has Cross-generational Behavioral Effectssupporting
confidence: 91%
“…To date, there have been over 40 published paternal preconception alcohol exposure studies in rodents (for review, see Finegersh et al., ), most varying in species, route of administration, and duration. Despite these differences, some intergenerational (F1) effects have been consistent such as low fetal and birthweight (Bielawski et al., ; Chang et al., , ; Ledig et al., ), altered organ weights (Abel, ; Chang et al., ; Ledig et al., ; Lee et al., ), and increased number of runts (Bielawski and Abel, ; Bielawski et al., ). Additional phenotypes reported include increased cortical thickness (Jamerson et al., ), reduced testosterone (Abel and Lee, ), and altered neurotransmitter levels (Nelson et al., ).…”
Section: Heritability Of Preconception Alcohol Exposurementioning
confidence: 99%
“…A comprehensive list of the ethanol exposures used and primary findings of these studies is shown in Table 1. Several groups have found that paternal ethanol induces physiologic abnormalities in offspring in the absence of maternal ethanol exposure, including low birth weight (Bielawski, Zaher, Svinarich, & Abel, 2002; Ledig et al, 1998), increased number of runts (Bielawski & Abel, 1997; Bielawski et al, 2002), altered organ weights (Abel, 1993b; Ledig et al, 1998; Lee et al, 2013), thickening of layers of the cerebral cortex (Jamerson, Wulser, & Kimler, 2004), and low testosterone levels (Abel, 1989b). Several behavioral abnormalities have also been noted, including decreased spatiotemporal learning (Wozniak, Cicero, Kettinger, & Meyer, 1991), decreased novelty-seeking behavior (Ledig et al, 1998), increased immobility on the forced-swim test (Abel & Bilitzke, 1990; Liang et al, 2014), and decreased grooming (Abel, 1991a).…”
Section: Effects Of Paternal Ethanol Exposure On Offspringmentioning
confidence: 99%